PELAKSANAAN LATIHAN TANGGA NADA DAN INTERVAL DENGAN METODE DRILL PADA EKSTRAKURIKULER PADUAN SUARA (UNISONO) DI SMP NEGERI 16 PADANG - Irma Yeni; Yensharti (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to describe the implementation of scale and interval exercises using a drill method during the choir extracurricular activities at SMP Negeri 16 Padang. Studying employs a qualitative approach with a descriptive method. Research informants consisted of the choir extracurricular instructor (as the primary informant) and five students (as supporting informants) selected through purposive sampling. Data was collected via observation, interviews, and documentation. The results indicate that the scale and interval exercises were conducted systematically, comprising planning, implementation, and evaluation stages. The exercises were carried out in a gradual and repetitive manner before being applied to the song "Indonesia Pusaka." The implementation of these exercises yielded positive results regarding the students' ability to distinguish between high and low pitches and execute pitch transitions more accurately, as well as boosting their confidence in participating in choir activities.